2022
DOI: 10.3390/ijms232113418
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Functional Analysis of VvWRKY28, a Vitis vinifera WRKY Transcription Factor Gene, with Functions in Tolerance to Cold and Salt Stress in Transgenic Arabidopsis thaliana

Abstract: The grape (Vitis vinifera L.) not only has a long history of cultivation, but also has rich nutritional value and high economic value. However, grapes often face many threats in the growth process. For example, low temperature and salt stress restrict the growth status, yield, and geographical distribution of grapes. WRKY, as one of the largest transcription factor (TF) families in plants, participates in the response of plants to stress. VvWRKY28, a new zinc finger type transcriptional regulator gene, was iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
(68 reference statements)
0
18
1
Order By: Relevance
“…The WRKY proteins are one of the largest and most important superfamilies of transcription factors (TFs) in plants. WRKY transcription factors encompass a core motif WRKYGQK (a highly conserved WRKY domain) at the N-terminus and an atypical Zinc finger motif at the C-terminus [ 12 ]. On the basis of both the number of WRKY domains and the features of the Zn-finger motif in their evolutionary history, the WRKY TFs can be divided into three different groups (I, II, and III).…”
Section: Introductionmentioning
confidence: 99%
“…The WRKY proteins are one of the largest and most important superfamilies of transcription factors (TFs) in plants. WRKY transcription factors encompass a core motif WRKYGQK (a highly conserved WRKY domain) at the N-terminus and an atypical Zinc finger motif at the C-terminus [ 12 ]. On the basis of both the number of WRKY domains and the features of the Zn-finger motif in their evolutionary history, the WRKY TFs can be divided into three different groups (I, II, and III).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, H 2 O 2 may also act as signalling molecules that activate related signalling pathways to regulate salt stress responses. In addition, Hsp20 might act as a chaperone protein to co‐regulate salt stress resistance together with other proteins, such as transcription factors FvMYB82 (from Fragaria vesca ), MbCBF1 (from Malus baccata ), and VvWRKY28 (from Vitis vinifera ), which are positive regulators of salt tolerance (Liu et al, 2022; Liang et al, 2022; Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…CsWRKY46 confers cold tolerance by modulating cold-stress-responsive genes in cucumber [ 37 ]. A cold-induced WRKY gene in grape, VvWRKY28 , regulated the expression of cold-stress-related genes and played a role in cold stress tolerance [ 38 ]. In this study, a CI-inducible WRKY TF, MaWRKY70, was identified.…”
Section: Discussionmentioning
confidence: 99%